Game performance versus competitive performance in the World Championship of handball 2011 - Gutiérrez, O.; Ruiz, J. L. (Journal of Human Kinetics, 2013)
This article assesses the game performance of the teams participating in the Men`s World Championship of Handball of 2011 by using Data Envelopment Analysis (DEA) and the cross-efficiency evaluation. DEA uses Linear Programming to yield a measure of the overall performance of the game of particular teams, and allows us to identify relative strengths and weaknesses by means of benchmarking analysis. The cross-efficiency evaluation provides a peerappraisal of the teams with different patterns of game, and makes it possible to rank them. Comparisons between this ranking and the final classification in the championship provide an insight into the game performance of the teams versus their competitive performance. We highlight the fact that France, which is the world champion, is also identified as an "all-round" performer in our game performance assessment.